Study of causative bacterial agents and risk factors predisposing to bacterial keratitis in Iraq - Munira Ch. Ismael; Aida H. Ibrahim; Raghad L. Kadim; Estabrak A. Mubarak (مجلة كلية الطب, 2017)
Background: Infective keratitis is the most common cause of blindness and preventable ocular morbidity worldwide. There are many published series of infective keratitis from both temperate and tropical parts of the world, and management strategies are well established1. Objective: The current study was aimed to detect the specific bacteria and predisposing factors that predisposed for the bacterial keratitis. Material and methods: Retrospective study of the hospital records of 40 patients who were diagnosed as bacterial keratitis and treated at the Ophthalmology in-patient department of at Ibn Al- haithum Teaching Hospital from May 2015 to December 2015.Patients who don’t have corneal scraping, or culture and sensitivity findings discarded from this study. Predisposing factors, clinical and microbiological data were reviewed. Corneal scrapings were obtained by physicians then were subjected for bacterial culture and biochemical tests. Results: Pseudomonas aeruginosa was the most common bacteria isolated at higher percentage 19(47.5%) cases whereas Klebsiella pneumoniae isolated at lower percentage 2(5%). The most common risk factors was foreign body in 10 (25%) followed by contact lenses in 8 (20%) patients. Conclusion: Gram negative bacteria were the most frequent bacterial organisms especially Pseudomonas aeruginosa isolated from corneal scraping and corneal ulcer was found to be occurring principally by foreign body followed by contact lens wearing.